Propuesta articular para la estructuración de la cadena funcional de valor en la constructora Ingeniería & construcciones M.D.J.S.A.S , ubicada en la ciudad de Barranquilla Colombia, Anàlisis del escenario de aplicaciòn en el año 2022 (2022)
This investigative document has the objective of proposing the structuring of the functional value chain of the Builder: Ingeniería & Construcciones MDJ S.A.S, analyzing the internal structure of the company, in order to position its products in the market, seeking to optimize the quality of goods. and services to attract more clients and suppliers, improving the commercial reach. This research is implemented through a descriptive design, under a mixed approach (qualitative - quantitative), this to analyze the internal problems of the Builder: Ingeniería & Construcciones MDJ S.A.S, and thus propose a business improvement to meet the market needs, are used a set of data analysis and interpretation methods through documentary analysis and theoretical review, based on the results obtained, the technological and innovative development of the company is optimized